A study of generic skills competencies among trainee teachers of Institut Perguruan Kampus Tengku Ampuan Afzan, Kuala Lipis, Pahang / Nurulafizan Salleh - Salleh, Nurulafizan (2014)
This paper discusses the generic skills competencies acquired by trainee teachers in general and it further explores the relationship with academic achievement, differences between gender, race or ethnicity group and program offered. A sample of 150 trainee teachers from Institut Perguruan Kampus Tengku Ampuan Afzan, Kuala Lipis, Pahang was surveyed using an inventory of 60 items. Descriptive and inferential statistics such as frequency analysis and Pearson's Product Moment Correlation analysis were employed in analyzing the data. The study found that the trainee teachers generally tend to respond positively to most of the components in prescribed generic skills but there is no relationship with their academic achievement.Male trainee teachers demonstrated higher possessed of generic skills compared to female trainee teachers. There is also significance different between Malay and Chinese ethnic group. Nevertheless, program that offered has no significant different with generic skills. The research has brought meaningful implications for trainee teachers, undergraduate students, educators, institute of higher learning, employer,and policy makers.